War baby/love child mixed race Asian American art - Kina, Laura, 1973-; Dariotis, Wei Ming (Book collections on Project MUSE., 2013)
War Baby / Love Child examines hybrid Asian American identity through a collection of essays, artworks, and interviews at the intersection of critical mixed race studies and contemporary art. The book pairs artwork and interviews with nineteen emerging, mid-career, and established mixed race/mixed heritage Asian American artists, including Li-lan and Kip Fulbeck, with scholarly essays exploring such topics as Vietnamese Amerasians, Korean transracial adoptions, and multiethnic Hawai'i. As an increasingly ethnically ambiguous Asian American generation is coming of age in an era of "optional identity," this collection brings together first-person perspectives and a wider scholarly context to shed light on changing Asian American cultures.